Justiça desportiva: muito além do julgamento por mero esporte - Simões, André Galdeano (2022)
This research work approaches the Sports Justice as an autonomous, complete and self-regulating ecosystem, addressing its problems, as well as the necessary aspects of professionalization facing the social economic transformation. We will approach the historical perspectives of the Sports Law in Brazil, since its birth until the current days: the formation of the Sportive Justice, its operation, composition and attributions in national forum and in comparative law, conceptualization of the sportive legal regimen, effectiveness of its independence, laws and own sportive principles that assert the necessity of judgments by specialized professionals, experts of the sportive lex